Design dimensions of corporate venture capital programs—a systematic literature review - Philipp Frey; Dominik K. Kanbach (Management Review Quarterly, 2023)
There is a plethora of research on organisational design elements of corporate venture capital (CVC) programs. However, the fragmented nature of this vein of corporate venturing research has led to an inconsistent picture regarding the organisational design of CVC programs. The goal of this study is to provide a holistic picture for both scholars and practitioners by integrating empirical research on the design of CVC programs. Therefore, the study employs a systematic literature review approach including a sample of 41 studies published from 1987 to 2023. For a systematic assessment of design elements of CVC programs, an inductive concept development approach is used to illustrate four main design dimensions–personnel, corporate relationship management, investment operating model and portfolio relationship management–which reflect 69 descriptive design elements. While previous studies have mainly looked at individual design dimensions of CVC programs from a strategic perspective, this paper presents comprehensive view on organisational structures of CVC programs by identifying building blocks of CVC design according to chosen objectives and available typologies. By specifying and allocating design dimensions to structural types and objectives of CVC programs, this study may also serve as a foundation for further research on the concepts which prevent high rates of early abandonment of CVCs.
Keywords: O03; M1; 650; Corporate venture capital; CVC; Organisational structure; Organisational design; Literature review